[Urogeriatric thinking using the example of antiandrogen therapy for prostate cancer]. - Wiedemann, A.; Manseck, A.; Stein, J.; Fröhner, M.; Fiebig, Christian; Piotrowski, A.; Kirschner-Hermanns, R. (Die Urologie, 2024)
The geriatric patient is defined by an age of over 75 years and multimorbidity or by an age of over 80 years. These patients exhibit a particular vulnerability, which, in the incidence of side effects or complications, leads to a loss of autonomy. Treatment sequalae, once they have arisen, can no longer be compensated. It is important to recognize and document treatment requirements among geriatric patients with the help of screening instruments such as the Identification of Seniors at Risk (ISAR) and Geriatric 8 (G8) scores. If a treatment requirement is identified, oncologic treatment should not be commenced uncritically but rather a focus placed on identification of functional deficits relevant to treatment, ideally using a geriatric assessment but at least based on a detailed medical history. These deficits can then be presented in a structured, examiner-independent, and forensically validated manner using special assessments. A planned treatment requires not only consideration of survival gains, but also knowledge of specific side effects and, in geriatric patients in particular, their impact on everyday life. These considerations should be compared with the patient's individual risk profile in order to prevent side effects from negating the effect of the treatment, for example by worsening the patient's self-help status. With regard to androgen deprivation in prostate cancer-which often is used uncritically-it is important to consider possible side effects such as osteoporosis, sarcopenia, anemia, and cognitive impairment in terms of a possible fall risk; an increase in cardiovascular mortality and the triggering of a metabolic syndrome on the basis of preexisting cardiac diseases or risk constellations; and to carry out a careful risk-benefit analysis.
EVALuna2:594139